2021
DOI: 10.1101/2020.12.28.20248875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speech pause distribution as an early marker for Alzheimer’s disease

Abstract: BackgroundPause duration analysis is a common feature in the study of discourse in Alzheimer’s disease (AD) and may also be helpful for its early detection. However, studies involving patients with amnestic mild cognitive impairment (aMCI) have yielded varying results.ObjectivesTo characterize the probability density distribution of speech pause durations in AD, two multi-domain amnestic MCI patients (with memory encoding deficits, a-mdMCI-E, and with retrieval impairment only, a-mdMCI-R) and healthy controls … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…However, the severity of this symptom depends on the stage of disease and is positively correlated with AD progression [ 45 , 46 , 47 ]. The distribution of speech pauses has been described as a marker for AD diagnosis [ 48 ]. Studies have shown that identification of language and diarization of speakers provide promising results for the diagnosis of speech loss in the case of AD [ 49 ].…”
Section: Shared Symptoms Of Asd and Admentioning
confidence: 99%
“…However, the severity of this symptom depends on the stage of disease and is positively correlated with AD progression [ 45 , 46 , 47 ]. The distribution of speech pauses has been described as a marker for AD diagnosis [ 48 ]. Studies have shown that identification of language and diarization of speakers provide promising results for the diagnosis of speech loss in the case of AD [ 49 ].…”
Section: Shared Symptoms Of Asd and Admentioning
confidence: 99%
“…These indicators encompass acoustic features, such as vocalisation features (i.e. speech-silence patterns) [4], paralinguistic features, such as fluency features [5] and speech pause distributions [6], as well as syntactic and lexical features extracted from speech transcripts [7].…”
Section: Introductionmentioning
confidence: 99%